Pemerintah Kabupaten dan penanggulangan kemiskinan di wilayah hutan di Indonesia - Andrianto, A.; Wollenberg, Eva Karoline; Cahyat, A.; Goenner, C.; Moeliono, M.; Limberg, G.; Iwan, R. (Center for International Forestry Research, 2006)
District governments in Indonesia are in the early stages of trying to reduce poverty in their areas. We explain the influences on district officials’ ability to effectively address poverty in two forest districts based on observations between 2003 and 2005. We found that centrally-imposed programs have created bureaucratic requirements that officials are reluctant to meet or prefer to use to their own benefit. District initiatives for economic development rarely reach the poor and even increase their vulnerability. This poor performance can be explained by weak incentives and institutions, unclear strategies and information and little participation of the poor themselves. District, provincial and central authorities need to ensure benefits for district officials who work to reduce poverty, have coherent, simple strategies, enable poor communities to voice their needs, revitalize coordination with funding and stronger leadership, and enable monitoring by districts and communities of government programs impacts on poverty.